River, Modernity, and Everyday Religion: An investigation on the New Spiritual Engagement between Society and River : - Wiwit Kurniawan; Tri Hidayati (CV. Inara, 2021)
This study aims to reveal the current view of modern society on rivers. Modernity has given a new view of nature and changed human behavior towards nature. Modern humans still keep the spirituality inherited from the past and welcome progress and rationality in the present as well. This study used a literature study as a research method. This study shows that there is a dilemma of community behavior over rivers. The spiritual bond between the community and the river still exists, but humans' behavior about destroying the river contradicts their beliefs.